Sustainable ways of managing for environmental services in Kathmandu Valley - Joshi, Jibgar (2008)

(untitled)
The paper deals with the worsening condition of the environment in Kathmandu Valley. It gives an analysis of the transformation of the Valley; and identifies the causes that have helped to sustain its ecology and social system. It tries to address how its identity and character have survived so far. It also looks into how the people and their culture linked with the economy of the Valley, played a positive role in the wise use of its resources in the past. The Valley is urbanizing at a rapid pace. This has led to many environmental problems; and the needs of the increasing population could not be met. People leave their native villages and come here to get some kind of work in an informal setting. Their incomes are so small that they can not afford most of the environmental services. This makes the environment deplorable for them to live or work. Most people in the Valley do not have access to adequate water and sanitation. There is an increasing shortage of water. The problems of solid waste management and the poor condition of roads have worsened the environment. The quality of life is declining due to pollution in terms of carbon emission, waste generation, noise, ugliness, and dirt. This clearly shows that there is an increasing incidence of slums in the Valley. As a result, the demand for a good local environment has increased. There is a tendency to locate modern activities in more pleasant areas. This is also clear from the differences in land values due to hedonic pricing. People get urban services in different ways. In the provision of these, the primary objective of the government is not to enhance the quality of environment as such. The paper examines why the provision of services has not improved the living conditions of the people. Despite huge investments in infrastructure, the needs of the people are not met. Nor has there been any increase in the physical assets that will help to meet the future needs. It looks at alternative ways of providing services. It highlights the relevance of traditional ways that people used to manage their ambience. It works on how these can be used to develop new areas while sustaining the ecological resources of the Valley. The paper finally suggests measures for the revival of traditional ways of living and their integration to support the Valley level service networks.